Community-Based Social Capital as a Pillar of Disaster Mitigation in Coastal Areas - Wati Rita; Sujianto; Heriyanto Meyzi; Adianto Adianto; Sutikno Sigit; Febrian Achmad Fajri (E3S Web of Conferences)
This article explores the influence of community-based social capital in disaster management within Bengkalis Regency, Riau Province, a region prone to natural disasters such as floods, landslides, whirlwinds, coastal abrasion, and erosion. Social capital—encompassing bonding, bridging, and linking dimensions—emerges as a pivotal element in disaster prevention and recovery. The research sample comprised local leaders, village officials, and members of community disaster preparedness groups. Data were collected from 73 respondents through a structured survey and analyzed using Structural Equation Modeling (SEM). The results highlight that community-based social capital is built upon shared values, norms, trust, and commitments, fostering robust social networks and relationships. These networks are instrumental in spreading information, enhancing disaster preparedness, fostering social solidarity, and bolstering community efforts in disaster mitigation. The article emphasizes the critical role of social capital in disaster-prone regions like Bengkalis and Rupat Islands and advocates for strengthened cross-sector collaboration between governmental and non-governmental entities to optimize disaster management strategies in both preand post-disaster contexts.